The hydrogen-induced pitting corrosion mechanism in duplex stainless steel studied by current-sensing atomic force microscopy. (December 2018) - Yakubov, Vladislav; Lin, Meichao; Volinsky, Alex; Qiao, Lijie; Guo, Liqiu
Abstract Duplex stainless steels have excellent corrosion resistance due to their two-phase microstructure and electrically insulating passive film. Nevertheless, hydrogen charging causes deterioration of the corrosion protection mechanisms, resulting in increased pitting susceptibility. In this study, current-sensing atomic force microscopy was used to investigate the electrical properties of the passive film formed on 2507 duplex stainless steel before hydrogen charging. Results were compared with optical images of pitting corrosion initiation after hydrogen charging and FeCl3 exposure. Highest passive film conductivity and current density were seen at grain boundaries, indicating poor passive film development and high pitting probability. High conductivity was also observed on the passive film located at the adjacent austenite phase, alluding to favorable conditions for pitting corrosion propagation. Phases were identified by magnetic force microscopy, while pit initiation with subsequent propagation after hydrogen charging and FeCl3 exposure was observed using optical microscopy. Pitting corrosion initiated at grain boundaries and propagated into the austenite grains. This study identified the pitting initiation and propagation mechanisms in 2507 duplex stainless steel.